Investigating the Effect of ICT on Human Development – Study of BRICS - Goel, Deepika (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : The long-run objective of this study was to analyze the impact of Information and Communication Technology (ICT) on the Human Development Index (HDI) for BRICS countries using annual data for the period from 2000–2022. Methodology : The long-term link between ICT and HDI for the BRICS countries from 2000 to 2022 was examined in the paper using panel cointegration and FMOLS approaches, taking into account control variables, including the gender inequality index, carbon emissions, GDP per capita, and population growth. Findings : Empirical findings demonstrated a strong long-term correlation between the GDP per capita, gender disparity, ICT, HDI, carbon emissions, and population growth rate. The grouped mean–FMOLS estimates’ signals agreed with theoretical theories regarding the relationships between the variables. While gender inequality and carbon emissions had a negative influence on HDI, ICT and GDP per capita exhibited a favorable benefit. A substantial causative relationship between HDI and ICT, GDP per capita, population growth, and carbon emissions was found by looking at Granger causality results. However, it was shown that gender inequality did not contribute to HDI. Practical Implications : The digitalization of services and digital payments has transformed the functioning of the economies to ensure inclusive and accelerated growth. Against this backdrop, the study analyzed the effect of ICT in promoting the development of human capital in the economy. BRICS was the choice of the sample as these countries have the potential to ride the digital progress in the global economy. Originality : This paper contributed to the literature by exploring the relationship between BRICS countries by incorporating different variables that can affect HDI. Moreover, in light of significant economic progress, the factors that affect human development keep on evolving in countries. New studies would help the countries gain useful insights in policy making.